Efficacy of Propolis-Based Mouthwash on Generalized Chronic Gingivitis: A Randomized Controlled Clinical Trial - Sargolzaie, Naser; Askari, Vahid Reza; Najjar, Maryam; Sargolzaie, Setayesh; Mirebeigi-jamasbi, Seyed Sepehr; Fasihi Ramandi, Mahdiye (Journal of Dental School, 2024)
Objectives This study aimed to investigate the effect of propolis-based mouthwash on the gingival parameters of generalized chronic gingivitis cases in a randomized controlled clinical trial. Methods A total number of 69 patients with generalized chronic gingivitis were randomly assigned into three groups (N=23): propolis, chlorhexidine, or placebo mouthwash. The gingival and bleeding indices were evaluated before and after two weeks of mouthwash use. Data analyses were performed using Kruskal-Wallis test, one-way analysis of variance, and paired t-test at p<0 .05. Results The average gingival index in the chlorhexidine group was significantly higher than in the propolis group (p=0.005), but there was no significant difference between the placebo and propolis mouthwash groups (p=0.080). Moreover, the average plaque index was significantly higher in the chlorhexidine group than the propolis group (p<0.001). However, no significant difference was observed between the placebo and propolis mouthwash groups (p=0.742). However, the average bleeding index in the chlorhexidine group was significantly lower than the propolis group (p=0.012), with no significant difference between the placebo and propolis mouthwash groups (p=0.134). Conclusion The present results showed that scaling and propolis mouthwash consumption significantly improved the bleeding on probing and the gingival indices compared to the placebo group. Therefore, this mouthwash can be useful for treating chronic generalized gingivitis.